Guideline attainment and morbidity/mortality rates in a large cohort of European haemodialysis patients (EURODOPPS). Issue 12 (1st April 2019) - Liabeuf, Sophie; Sajjad, Ayesha; Kramer, Anneke; Bieber, Brian; McCullough, Keith; Pisoni, Ron; Caskey, Fergus; Combe, Christian; Robinson, Bruce M; Jager, Kitty J; Massy, Ziad A
Abstract: Background: Haemodialysis patients experience a wide variety of intermediate complications, such as anaemia, hypertension and mineral bone disease (MBD). We aimed to assess the risk of death and hospital admissions as a function of the simultaneous attainment of different guideline targets (for hypertension, anaemia and MBD) in a large European cohort of dialysis patients. Methods: EURODOPPS is part of the Dialysis Outcomes and Practice Patterns Study (DOPPS) international, prospective cohort study of adult, in-centre haemodialysis patients for whom clinical data are extracted from medical records. In the present analysis, 6317 patients from seven European countries were included between 2009 and 2011. The percentages of patients treated according to the international guidelines on anaemia, hypertension and MBD were determined. The overall degree of guideline attainment was considered to be high if four or all five of the evaluated targets were attained, moderate if two or three targets were attained, and low if fewer than two targets were attained. Fully adjusted multivariate Cox models were used to investigate the relationship of target attainment with mortality and first hospital admission. Results: At baseline, the degree of target attainment was low in 1751 patients (28%), moderate in 3803 (60%) and high in 763 (12%). In the fully adjusted model using time-dependent covariates, low attainment was associated with higher all-cause mortality [hazard ratio (95% confidence interval) = 1.19 (1.05–1.34)] and high attainment was associated with lower all-cause mortality [0.82 (0.68–0.99)]. In a similar model that additionally accounted for death as a competing risk, low and high attainments were not associated with hospital admission. Conclusion: In a large international cohort of dialysis patients, we have shown that more stringent application of guidelines is associated with lower mortality.